Online brand image, luxury value perception and brand equity - Wang, Fei; Wong, Chee Hoo; Ng, Alex, Hou Hong; Lim, Kim Yew (INTI International University, 2019)
Brand image generates value for luxury companies and helps build long term brand equity. Many luxury brand companies nowadays adopt mass marketing approach with embedding luxury code to prevent their prestige brand image from being diluted. It is crucial for marketers, against a background of online brand-consumer communication, understanding the fast-changing luxury consumers' perception of luxury brands. This study highlights the developments in the existing literature on the issues of brand image on consumer perception of luxury value and brand equity. The main purpose of this paper is to develop a plausible theoretical framework with several hypotheses to help the future investigation of the effect of online brand image on brand equity and consumer perception of luxury value. Finally, this paper discusses the new framework at the theoretical level before contributing to research. It is proposed that brand image exerts considerable influence on brand equity. Besides, consumer perception of luxury value has a mediating effect on the relationship between online brand image and brand equity of luxury brands. This study will provide relevant information for luxury marketers to assist in shaping online brand image and building brand equity. On the other hand, the research propositions of the paper are drawn from the extant literature and theoretical discussion, which requires empirical testing